Ways of Knowing: A Qualitative Study of Mental Health Professionals’ Epistemic Practices in Psychiatry - Jonathan Munch Bach; Svend Brinkmann; Henriette Bruun (Qualitative Health Research, 2026)
The purpose of this article is to explore the various ways mental health professionals produce knowledge about patients’ condition in practice. The study is based on empirical material from four months of participant observation and interviews with mental health professionals in both inpatient and outpatient clinics located in Denmark. In the article, we demonstrate how mental health practitioners’ ways of knowing in everyday practice is made up of various epistemic practices. Epistemic practices, to varying degrees, deviate from what we call the standard epistemology of psychiatry. To understand those epistemic practices, we propose that mental health practitioners should be understood as craftspersons . Finally, we suggest the notion of situated rationality as an important term to understand their ways of knowing.